Employee Training and Retention: A Correlation Study among the Employees of Engineering Industry in Coimbatore - Jayanthi, R.; Arumugam, Dharmaraj (International Journal of Psychosocial Rehabilitation, 2019)
Today’s competitive environment requires organizations to equip their employees with adequate skills and knowledge to combat the situation. Employee retention and turnover are found to be the challenging task of an organization. The organizations are striving to find strategies to improve retention and reduce turnover of their employees. Training and development are important functions which may have a significant influence on the outcomes of the organizations. Thus, a study was carried out to understand the association between employee training and their retention.